Anatomical optical coherence tomography for long-term, portable, quantitative endoscopy - Leigh, M.; Armstrong, J.; Paduch, A.; Walsh, J.; Hillman, D.; Eastwood, Peter; Sampson, D. (IEEE, 2008)
In this paper, we report on anatomical optical coherence tomography, a catheter-based optical modality designed to provide quantitative sectional images of internal hollow organ anatomy over extended observational periods. We consider the design and performance of an instrument and its initial intended application in the human upper airway for the characterization of obstructive sleep apnea (OSA). Compared with current modalities, the technique uniquely combines quantitative imaging, bedside operation, and safety for use over extended periods of time with no cumulative dose limit. Our experiments show that the instrument is capable of imaging subjects during sleep, and that it can record dynamic changes in airway size and shape. © 2006 IEEE.